Hasil Belajar Teknik Dasar Sepak Bola melalui Pembelajaran Berdiferensiasi - Fredik Edison Nope; Yahya Jacson Palinata; Alventur Baun; Andry Sinlaeloe (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
The purpose of this study is to examine learning outcomes in basic soccer skills through differentiated instruction. This research uses a descriptive research design with a quantitative approach, and the research method used is quantitative with the implementation stages of finding the value of independent variables, either from one or more variables (independent) without making comparisons or connecting them to other variables. Observation sheets and test sheets are used as research instruments. The results of the study show that the differentiated learning model was implemented “well” based on cognitive, affective, and psychomotor tests. Psychomotor tests showed a significant improvement in students' motor skills, especially in learning passing, controlling, and dribbling techniques. Conclusion, based on the results of research and discussion on the learning outcomes of basic soccer techniques through differentiated learning, it can be concluded that the differentiated learning model applied at North Mollo 1 Christian Middle School to teachers for the Content (Input), process and product (output) indicators are all available and implemented well. Keywords: Learning Outcomes, Differentiated Instruction